Sobre pessoas, pedras e formigas : relações simbiopoéticas na escultura de pedra-sabão mineira - Victória Carolina Pinheiro Lopes Dias (2023)
Minas Gerais has had, since the colonial period, a significant production of material culture linked to soapstone, specially in the cities of Mariana and Ouro Preto. Current production is concentrated in districts and sub-districts of these cities. It is common to find in these localities small productive units that are extensions of the houses of artisans. This setting offers a context rich in experiences that cross the creative and productive processes of sculpted things. This thesis is an ethnography of the creative pluriverse of master sculptor Duilo Bretas, who lives at Cachoeira do Campo, district of Ouro Preto. I refer to him as a master due to the learning relationship we have established and to his recognition as such by many artisans in the region. The master-disciple relationship allowed this work to be based on learning, creation, exchange, experience and collaboration. Based on the microcosm of the master craftsman, this study sought to investigate the nature of the relationships between people and stone things. It aimed to demonstrate that the uncovering of these relationships can broaden the narratives of what the different beings involved in the process of composing sculptures do, and thus welcome the existential pluralism of beings and things. The methodological path was fluid like the course of a river, as it was oriented by the rhythms and movements of life in which I was able to participate. Working with a certain methodological freedom allowed me to create correspondences between different types of knowledge and to adopt practices and specific modes of proceeding inspired by counter-inductive methods, such as the theory “against the method”. The motto of diverse knowledge incited me to create a textual narrative in which the arguments were not restricted to written textuality; drawings and photographs inhabit the text as part of the narrative. In the end, I was able to observe that the rela-tionships between people and stone things, in the process of composing sculptures, are as diverse as the beings that participate each one in their own way in this composition.